THE INFLUENCE OF TRAINING, COMMUNICATION, INFORMATION TECHNOLOGY AND LEADERSHIP ON IMPLEMENTATION OF KNOWLEDGE MANAGEMENT IN STATE CORPORATIONS - AKINYI, BENTER ALICE; Abok, Dr. Alice (IJRDO - Journal of Applied Management Science, 2015)
Knowledge management (KM) is a formalized, integrated approach to identifying and managing an organization’s knowledge assets. The main purpose of this study was to investigate factors affecting the implementation of knowledge management in State Corporations in Kenya. More specifically the study sought to evaluate the influence of training, communication, information technology and knowledge leadership on knowledge management. Studies done on knowledge management have focused on comparisons on public and private sector use of knowledge. Others have examined how knowledge management practices are carried out in both the Public and Private Sectors. To add the existing literature, the study investigated factors affecting the implementation of knowledge management in state corporations. The study concentrated on the factors; Training, Communication, Information Technology and Knowledge Leadership. Descriptive research was used in the research. The target population was state Corporations in Kenya, while the study population was middle level managers of the state corporation within the state Department of Agriculture. The Sample size was 100 middle level managers. Primary data was collected using a questionnaire. A pilot test was conducted to establish the validity and reliability of the questionnaire. Regression analysis was used to establish to what extent each variable affects the dependent variable. Data presentation was done using tables, pie charts, averages, frequencies. Analysis was done using SPSS V.21 to assist in analyzing data. The study sought to establish the factors affecting knowledge management implementation in state corporations Case of State Department of Agriculture and whether training, communication, information technology and knowledge leadership will affect the implementation of knowledge management in state corporations. Results from regression model of knowledge management implementation on organizational leadership, communication, information technology and training revealed that the coefficients for training, communication and information technology were significant at 5% level of significance. Therefore, knowledge management implementation can be predicted using training, communication and information technology. However, the coefficient for organizational leadership was not significant.